2019
DOI: 10.1038/s41423-019-0243-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of IL4 controls iNKT cell-DC crosstalk in tumors

Abstract: The spatiotemporal distribution of cytokines orchestrates immune responses in vivo, yet the underlying mechanisms remain to be explored. We showed here that the spatial distribution of interleukin-4 (IL4) in invariant natural killer T (iNKT) cells regulated crosstalk between iNKT cells and dendritic cells (DCs) and controlled iNKT cell-mediated T-helper type 1 (Th1) responses. The persistent polarization of IL4 induced by strong lipid antigens, that is, α-galactosylceramide (αGC), caused IL4 accumulation at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Elevated expression of Acvr1, Baiap2 and Fgd4 in intratumoral iNKT cells from Vcam1 knockdown MC38 tumors indicated improved CDC42 signaling, which is a Rho family small GTPase [43][44][45] . In line with previous study 46 , we found that expression of CDC42 was reduced in intratumoral iNKT cells (Fig. 5f).…”
Section: Tumor Vcam1 Impairs Intratumoral Inkt Cell Motility and Acti...supporting
confidence: 93%
“…Elevated expression of Acvr1, Baiap2 and Fgd4 in intratumoral iNKT cells from Vcam1 knockdown MC38 tumors indicated improved CDC42 signaling, which is a Rho family small GTPase [43][44][45] . In line with previous study 46 , we found that expression of CDC42 was reduced in intratumoral iNKT cells (Fig. 5f).…”
Section: Tumor Vcam1 Impairs Intratumoral Inkt Cell Motility and Acti...supporting
confidence: 93%
“…α-GalCer is a synthetic glycolipid which binds to the nonclassical MHC-I molecule, CD1d, on APCs and activates Type 1 NKT cells. By activating NKT cells, the glycolipid α-GalCer induces maturation of DCs via CD40L presentation and cytokines such as IL-4, facilitating subsequent responses by conventional CD4 + and CD8 + T cells [38][39][40]. We chose α-GalCer as an adjuvant in the context of HKS vaccination because of its proven role in mediating protection against murine malaria [41] by enhancing malaria-specific CD8 + T-cell responses [33].…”
Section: Discussionmentioning
confidence: 99%
“…Crosstalk between these cells improves Th1 cell immune responses, which is mediated under the control of cell division control protein 42 homolog (Cdc42). The Cdc42 significantly controls cell migration and interaction, which decreased expression of Cdc42 in NKT cells and destroyed the intratumoral interaction and activation of NKT cells [ 50 , 110 ]. The last challenge facing the advancement of CAR-NKT cell therapy is persistence duration in TME.…”
Section: Challenges In Car-nkt Cell Therapymentioning
confidence: 99%
“…One of the other solutions to improving cancer treatment is the enhancement function of NKT cells in TME and better recognition of Th1-based lipid antigens [ 110 ]. For example, IL-15 co-expression in CAR-NKT cells increases their localization at the tumor site and improves tumor control without any toxic effects.…”
Section: Safety and Efficacy Imrovemment Strategiesmentioning
confidence: 99%